LOCAL LEVELS OF PROINFLAMMATORY AND IMMUNOSUPPRESSIVE CYTOKINES DURING EXACERBATION OF CHRONIC OBSTRUCTIVE PULMONARY DISEASE - Куюн, Л.О. (World of Medicine and Biology, 2016)
The study included 104 patients with Chronic Obstructive Pulmonary Disease (COPD). The control group included 98 healthy individuals. Results of the study found that COPD exacerbation leading to high inflammatory activity at local level. There was observed a significant (p